A new species of Keysercypria Karanovic (Crustacea: Ostracoda) from Argentina - Díaz, Analía R.; Lopretto, Estela C. (Zootaxa, 2011)
In her revision on Recent Cyclocypridinae, Karanovic (2011) erected the new genus Keysercypria, endemic of the Neotropical Realm. The aim of this study is to describe and illustrate a new species within the genus recorded from the lower Parana region, according to the recently proposed division of the world freshwater ecosystems (www.feow.org). The new species represents the most southern record of the genus.